THE ROLE OF WORK STRESS, RESILIENCE AND COMPETENCY ON COMPANIES EMPLOYEE PERFORMANCE IN SURABAYA - Pratiwi, Dian Arinda Puspita; Mujanah, Siti (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
This study aims to determine and analyze Job Stress, Resilience and Competence partially or simultaneously on the Employee Performance. This study uses the entire population of 75 employees of Companies in Surabaya through the distribution of questionnaires using quantitative data types. The results showed that the t-test analysis for the work stress variable had a negative and no significant effect on employee performance. Resilience and Competence variables have a positive or significant effect on employee performance. And the results of the F test indicate that the variables of Work Stress, Resilience and Competence simultaneously significantly affect on employee performance, this imply that Resilence of the employees and Competence were importante to increasing Job performance of the employees in the Company.